Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Dung Vu

Giải phương trình sau : \(\dfrac{x^2+3x+2}{x-3}\left(x+1\right)=\dfrac{x^2+3x+2}{x-3}\left(x^2-2x-7\right)\)

nthv_.
20 tháng 11 2021 lúc 17:33

\(ĐK:x\ne3\\ PT\Leftrightarrow\dfrac{x^2+3x+2}{x-3}\left(-x-1+x^2-2x-7\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}\dfrac{\left(x+1\right)\left(x+2\right)}{x-3}=0\\x^2-3x-8=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=-1\\x=-2\\x=\dfrac{3+\sqrt{41}}{2}\\x=\dfrac{3-\sqrt{41}}{2}\end{matrix}\right.\)